Biosorption of methylene blue from aqueous solution using kenaf derived biochar: batch and desorption studies - Muhammad Omar, Muhammad Navin (2020)
The removal of methylene blue dye from aqueous solution using kenaf derived biochar has been investigated. Desorption studies were also been conducted. Batch biosorption studies has been carried out by observing the effect of experimental parameters including biosorbent dosage, pH, initial methylene blue dye concentration and temperature. Biosorption experiments were carried at different parameters of biosorbent dosage of (1,2&3g), initial methylene blue dye concentration of (100,150&200 mg/L), at pH of (4,7&9) and temperature of (30,40&50°C) to determine the highest methylene blue dye removal of biochar with high adsorption affinity. The optimum condition for the biosorption of methylene blue dye were (biosorbent dosage 3 g, initial methylene blue dye concentration = 1.00 mg/L, pH = 4, temperature ---- 40°C). The highest removal efficiency was recorded at 97.724197 %. For the characterisation of the raw kenaf, biochar, batch experiments and desorption, FTIR, BET and XRD were used.